2015
DOI: 10.1152/ajpgi.00269.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity on severity of colitis and cytokine expression in mouse mesenteric fat. Potential role of adiponectin receptor 1

Abstract: In inflammatory bowel disease (IBD), obesity is associated with worsening of the course of disease. Here, we examined the role of obesity in the development of colitis and studied mesenteric fat-epithelial cell interactions in patients with IBD. We combined the diet-induce obesity with the trinitrobenzene sulfonic acid (TNBS) colitis mouse model to create groups with obesity, colitis, and their combination. Changes in the mesenteric fat and intestine were assessed by histology, myeloperoxidase assay, and cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 51 publications
4
41
0
Order By: Relevance
“…These data are in agreement with other cellular stress systems where Adi-poR1 is necessary to reduce cellular damage and apoptosis (34,35). Importantly, it has been recently demonstrated that intracolonic injection of AdipoR1 siRNA worsens colitis in mice, thus reinforcing our observations (36). Taken together, these data suggest that APN through AdipoR1 is critical for maintaining IEC survival.…”
Section: Discussionsupporting
confidence: 92%
“…These data are in agreement with other cellular stress systems where Adi-poR1 is necessary to reduce cellular damage and apoptosis (34,35). Importantly, it has been recently demonstrated that intracolonic injection of AdipoR1 siRNA worsens colitis in mice, thus reinforcing our observations (36). Taken together, these data suggest that APN through AdipoR1 is critical for maintaining IEC survival.…”
Section: Discussionsupporting
confidence: 92%
“…The frequent consumption of an empty-caloric diet, without physical activity, increases fat storage and results in obesity, hepatomegaly and T2DM [29]. Indeed, in the HF-EFr group, visceral fat was more pronounced and serum leptin levels were higher, similar to changes reported in patients [30]. Liver weight was highest in response to the HF-EFr-diet, and was associated with a significant progressive increase in intrahepatic triglyceride content as a result of expression of Fasn .…”
Section: Discussionmentioning
confidence: 64%
“…insulin sensitivity), glucose metabolism, vascular and immune function making them key players in the pathogenesis of obesity, type 2 diabetes, metabolic syndrome, hypertension, atherosclerosis, inflammatory‐related diseases (e.g. inflammatory bowel disease) or colorectal cancer …”
Section: Introductionmentioning
confidence: 99%
“…inflammatory bowel disease) or colorectal cancer. [10][11][12][13][14][15][16] In recent years, much effort has been spent on uncovering the role of the fatty acid binding protein 4 (FABP4; aP2; AFABP), a small cytosolic protein (14-15 kDa) that is preferentially expressed in adipocytes and macrophages. Alterations in the expression of FABP4 have been implicated in the pathogenesis of obesity, metabolic syndrome, cardiovascular disease, and inflammation.…”
Section: Introductionmentioning
confidence: 99%